PENGARUH KARAKTERISTIK DEWAN DIREKSI TERHADAP KINERJA KEUANGAN DENGAN REPUTASI PERUSAHAAN SEBAGAI VARIABEL MEDIASI - Robert Jao; Marselinus Asri; Anthony Holly; Rivaldy (Jurusan Akuntansi Fakultas Ekonomi Dan Bisnis Universitas Mataram, 2022)
This research was aimed to investigate the role of director’s board size, director’s board skill, and women’s presence on director’s board as mechanisms to improve firm’s reputation as mediating effect on financial performance. This research used secondary data obtained by using documenter method. The data source in this research was the annual reports of non-financial companies listed on the Indonesia Stock Exchange (IDX) for the period 2016 to 2019. The sample were selected using purposive sampling method, with a total of 64 companies and analyzed used path analysis. The result of this research indicate that director’s board size had a positive and significant on firm reputation and financial performance. Director’s board skill had a positive and significant on firm reputation and financial performance. Women’s presence on director board had a positive and nonsignificant on firm reputation and financial performance. Firm’s reputation had a positive and significant on financial performance. The sobel test result indicated that firm’s reputation mediated the effect of director’s board size and director’s board skill on financial performance and belong to partial mediation type. The sobel test result indicate that firm’s reputation didn’t mediate the effect of women’s presence on director’s board on financial performance.